1995
DOI: 10.1172/jci118059
|View full text |Cite
|
Sign up to set email alerts
|

Acute blockade of nitric oxide synthase inhibits renal vasodilation and hyperfiltration during pregnancy in chronically instrumented conscious rats.

Abstract: Because the kidneys are vasodilated and the endogenous production of nitric oxide is increased in gravid rats, we tested whether nitric oxide mediates the renal vasodilatory response to pregnancy. Chronically instrumented, conscious rats of gestational days 12-14 were studied concurrently with age-matched virgin control animals. GFR and effective renal plasma flow (ERPF) were determined by the renal clearances of inulin and para-aminohippurate before and during acute infusion of NW-nitro-L-arginine methyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 39 publications
11
102
1
1
Order By: Relevance
“…This renal vasodilatory effect does not require the presence of the ovaries (25) and is also observed during relaxin administration to male rats (26). Relaxin administration to nonpregnant female rats also diminishes the renal vasoconstrictor response to angiotensin II, similar to the dampening influence of rat gestation (25,27,28). Moreover, reduced myogenic reactivity of small renal arteries is observed after relaxin administration, analogous to vessels isolated from midterm pregnant rats (29,30).…”
Section: Newer Aspects On Relaxin In Pregnancy and Preeclampsiamentioning
confidence: 77%
“…This renal vasodilatory effect does not require the presence of the ovaries (25) and is also observed during relaxin administration to male rats (26). Relaxin administration to nonpregnant female rats also diminishes the renal vasoconstrictor response to angiotensin II, similar to the dampening influence of rat gestation (25,27,28). Moreover, reduced myogenic reactivity of small renal arteries is observed after relaxin administration, analogous to vessels isolated from midterm pregnant rats (29,30).…”
Section: Newer Aspects On Relaxin In Pregnancy and Preeclampsiamentioning
confidence: 77%
“…Therefore, we speculate that although NO may contribute to the maintenance of reduced vessel tone in some vascular regions during pregnancy (e.g. uteroplacental (Conrad et al, 1993a,b), renal (Danielson & Conrad, 1995)), the reduced total peripheral resistance, at least in rabbits, is mediated by an as yet unidentified mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…The proposed mechanism of relaxin involves an increase in vascular gelatinase activity, which upregulates NO-dependent vasodilation via the endothelin-B NO pathway (14). In pregnant rats, investigators have convincingly demonstrated increments in endogenous production of NO (15), and through acute or chronic inhibition of NO synthase, investigators have demonstrated abolishment of the glomerular hyperfiltration in pregnancy (16,17). Hence, NO is necessary for the hemodynamic adaptation in renal function during pregnancy, and relaxin may represent a pregnancy-specific mechanism for augmenting the effects of NO.…”
Section: Renal Functionmentioning
confidence: 99%